PENGELOLAAN ADMINISTRASI DAN KEUANGAN PONDOK PESANTREN BAHRUL ULUUM PURBALINGGA - Ratu Ayu Sri Wulandari MA (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
The administrative and financial management of Islamic boarding schools is a crucial component that determines the smooth running of Islamic boarding schools’ activities. However, in reality, there are still many administrative and financial management of Islamic boarding schools that cannot be separated from various problems. The purpose of this service program is to provide understanding and assistance to the implementation of administrative and financial management of Islamic boarding schools. This service program is carried out at the Bahrul Uluum Islamic Boarding School in Cipawon Village, Bukateja District, Purbalingga Regency, Central Java. The target audience is the administrators of Islamic boarding schools. After this program is completed, it is hoped that the administrators (managers) of Islamic boarding schools can gain knowledge and can apply directly how to manage the administration and finances of Islamic boarding schools properly, effectively, and efficiently. This PKM activity begins with a survey process on problems, counseling or material delivery, and mentoring in administrative and financial management practices.